Analyzing Regional Variation in Health Care Utilization Using (Rich) Household Microdata - Peter Eibich; Nicolas R. Ziebarth (Health Policy, 2014)
This paper exploits rich SOEP microdata to analyze state-level variation in health care utilization in Germany. Unlike most studies in the field of the Small Area Variation (SAV) literature, our approach allows us to net out a large array of individual-level and state-level factors that may contribute to the geographic variation in health care utilization. The raw data suggest that state-level hospitalization rates vary from 65 to 165 percent of the national mean. Ambulatory doctor visits range from 90 to 120 percent of the national mean. Interestingly, in the former GDR states, doctor visit rates are significantly below the national mean, while hospitalization rates lie above the national mean. The significant state-level differences vanish once we control for individual-level socio-economic characteristics, the respondents health status, their health behavior as well as supply-side state-level factors.
Additional information: NOTICE: This is the author's version of a work that was accepted for publication in Health Policy. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for publication. A definitive version was subsequently published in Health Policy 114 (2013), 1, pp. 41-53 and is online available at http://dx.doi.org/10.1016/j.healthpol.2013.04.015.
Keywords: I11; I12; I14; I18; 330; Small Area Variation; Health care utilization; SOEP; Gesundheitswesen; Bundesrepublik Deutschland